Forbearance A Theological Ethic for a Disagreeable Church - Davis, James Calvin (Grand Rapids William B. Eerdmans Publishing Company, 2017)
What happens when we approach disagreements in our churches not as problems to solve but as opportunities to practice Christian virtue? In this book James Calvin Davis reclaims the biblical concept of forbearance to develop a theological ethic for faithful disagreement. Pointing to Ephesians and Colossians, in which Paul challenged his readers to "bear with each other" in spite of differences, Davis draws out a theologically grounded practice in which Christians work hard to maintain unity while still taking seriously matters on which they disagree. The practice of forbearance, Davis argues, offers Christians a dignified, graceful, and constructive way to deal with conflict. Forbearance can also strengthen the church's public witness, offering an antidote to the pervasive divisiveness present in contemporary culture. --
Intro -- Title Page -- Copyright -- Contents -- Preface -- Acknowledgments -- 1. Forbearance and Biblical Character -- 2. Humility -- 3. Patience and Hope -- 4. Wisdom -- 5. Faithfulness -- 6. Friendship -- 7. Truth -- 8. Justice -- 9. Forbearance as Social Witness -- Appendix -- Notes -- Selected Bibliography -- Index of Names and Subjects -- Index of Scripture References
Includes bibliographical references and indexes
Online-Ausg.
Keywords: Virtues; Virtue; Conflict Management -- Religious aspects -- Christianity; Patience -- Religious aspects -- Christianity; Church controversies